Pengembangan Produk Pangan Darurat Berbasis Umbi Talas Bogor (Colocasia esculenta L. Schott) dan Kacang Tunggak (Vigna unguiculata L. Walp) : Tinjauan Sifat Fisik dan Kadar Proksimat (Jurnal Nutrire Diaita (Ilmu Gizi), 2023)
One of the requirements for emergency food for disaster victims is have a high density of nutrients. Taro tubers have a high protein and iron (fe) content while cowpea has a high protein, namely 18.3%–25.53%. Bogor taro tubers and cowpea can be processed into flour and then used as an ingredient for making cookies. This study was completely randomized design (CRD) with 2 repetitions, 2 experimental units and 4 variations. There were 4 variations in the ratio of Bogor taro tuber flour and cowpea flour, namely 25% : 0% (A), 25% : 15% (B), 25% : 25% (C), and 25% : 35% (D). The physical properties of the texture were tested using the Universal Testing Machine (UTM), the proximate levels were water with gravimetry, ash with dry ashing, protein with kjeldahl, fat with soxhlet, carbohydrates with by difference. Statistical analysis using the Kruskal-Wallis and Mann Whitney tests. There was an effect of variations in the treatment to the physical properties of the texture (p = 0.012). Cookies that have a good texture was cookies C (8.77 N). Based on SNI requirements, all cookies only met the requirements for water, energy, protein and fat. Based on the nutritional requirements for emergency food, only met for carbohydrates requirement. Mixing Bogor taro tuber flour with various additions of cowpea affected the physical properties (texture) and proximate levels. However, reformulation was needed so that cookies can meet emergency food standards.